Indigenous knowledge: Protecting the lions' share - Iongh, Hans de (Technical Centre for Agricultural and Rural Cooperation, 2008)
Combining satellite and mobile phone technology with knowledge from nomadic herdsmen in Cameroon will help prevent confl ict between livestock and predatory lions.